ANALISIS PENGARUH KUALITAS LAYANAN DAN KEPERCAYAAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIATOR (Studi pada Pengguna Jasa PT. Pos Indonesia di Semarang) - Annisa, Annisa; Dwiyanto, Bambang Munas (Diponegoro Journal of Management, 2021)
ABSTRACT PT. Pos Indonesia is a state-owned company (BUMN) that operates in the service of sending letters, packages and money. The emergence of various courier service options in Indonesia has caused intense competition between PT. Pos Indonesia with private courier companies, such as JNE, J&T Express, and Tiki. The market which was originally a monopoly market with PT. Pos Indonesia, as a major player, is currently being eroded by the very rapid development of private courier companies. Tight competition also occurs in the financial services sector, with the emergence of various companies creating digital wallet applications that make it easier for users to make financial transactions wherever and whenever they want such as GoPay, DANA, OVO, and others. This study aims to analyze how much influence the service quality, trust and customer satisfaction on customer loyalty to use the services of PT. Pos Indonesian. The sample used in this study was the people of Semarang City who have used the courier service of PT. Pos Indonesia in the last one year. The sample was 167 respondents. The sample collection method used purposive sampling. The data collection method was distributing questionnaires online via google form. This research used Structural Equation Modeling (SEM) analysis with AMOS 24.0 analysis tools. The results of this study indicate that service quality and trust have a positive and significant effect on customer satisfaction and customer loyalty. In addition, customer satisfaction has a positive and significant effect on customer loyalty.